The subthalamic nucleus keeps you high on emotion: behavioral consequences of its inactivation - Pelloux, Yann; Meffre, Julie; Giorla, Elodie; Baunez, Christelle (Frontiers in Behavioral Neuroscience, 2014)
The subthalamic nucleus (STN) belongs to the basal ganglia and is the current target for the surgical treatment of neurological and psychiatric disorders such as Parkinson’s Disease (PD) and obsessive compulsive disorders, but also a proposed site for the treatment of addiction. It is therefore very important to understand its functions in order to anticipate and prevent possible side-effects in the patients. Although the involvement of the STN is well documented in motor, cognitive and motivational processes, less is known regarding emotional processes. Here we have investigated the direct consequences of STN inactivation by excitotoxic lesions on emotional processing and reinforcement in the rat. We have used various behavioral procedures to assess affect for neutral, positive and negative reinforcers in STN lesioned rats. STN lesions reduced affective responses for positive (sweet solutions) and negative (electric foot shock, Lithium Chloride-induced sickness) reinforcers while they had no effect on responses for a more neutral reinforcer (novelty induced place preference). Furthermore, when given the choice between saccharine, a sweet but non caloric solution, and glucose, a more bland but caloric solution, in contrast to sham animals that preferred saccharine, STN lesioned animals preferred glucose over saccharine. Taken altogether these results reveal that STN plays a critical role in emotional processing. These results, in line with some clinical observations in PD patients subjected to STN surgery, suggest possible emotional side-effects of treatments targeting the STN. They also suggest that the increased motivation for sucrose previously reported cannot be due to increased pleasure, but could be responsible for the decreased motivation for cocaine reported after STN inactivation.